2011
DOI: 10.1111/j.1872-034x.2011.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics of non‐cancerous liver tissue in non‐B non‐C hepatocellular carcinoma

Abstract: Although chronic infection with hepatitis B virus (HBV) and/or hepatitis C virus (HCV) are the most important risk factors for the development of hepatocellular carcinoma (HCC) worldwide, the proportion of HCC patients negative for the hepatitis B surface antigen and hepatitis C antibody, so-called "non-B non-C HCC", is rapidly increasing, especially in Japan. The background liver diseases of non-B non-C HCC patients can be multifactorial, including occult HBV infection and non-alcoholic steatohepatitis. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 84 publications
(162 reference statements)
0
26
1
Order By: Relevance
“…Similarly, in Japan, an HCV‐endemic area, the proportion of NBNC‐HCC was 6.8%‐10% before 2000, but by 2009, this had increased to 17.3%‐19% 27, 28, 29, 30, 31, 32. A retrospective study by Tateishi et al28 revealed that the proportion of patients with HCC with nonviral etiologies increased from 10.0% in 1991 to 24.1% in 2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in Japan, an HCV‐endemic area, the proportion of NBNC‐HCC was 6.8%‐10% before 2000, but by 2009, this had increased to 17.3%‐19% 27, 28, 29, 30, 31, 32. A retrospective study by Tateishi et al28 revealed that the proportion of patients with HCC with nonviral etiologies increased from 10.0% in 1991 to 24.1% in 2010.…”
Section: Discussionmentioning
confidence: 99%
“…The category NBNC‐HCC indicated that a patient tested negative for all three viral markers: HBsAg, HBV DNA (undetectable), and anti‐HCV. In published reports, the diagnosis of NBNC‐HCC only required negative results for both HBsAg and anti‐HCV,27, 28, 29, 30, 31, 32, 33, 34 and tests for serum HBV DNA were not performed. In this study, we added HBV DNA criteria (undetectable) for the diagnosis of NBNC‐HCC because among the 2,153 patients with HBV‐HCC and the 310 patients with B+C‐HCC in our detailed viral marker study report, we identified 202 patients (8.20%) who tested negative for HBsAg but positive for HBV DNA 26.…”
mentioning
confidence: 99%
“…Although most cases of this malignancy are associated with viral infections such as hepatitis B virus (HBV) and hepatitis C virus (HCV) infections, a substantial proportion of HCC patients are negative for markers of HBV surface antigen (HBsAg) and HCV antibody (HCVAb) [non-B non-C HCC (NBNC-HCC)]. The frequency of NBNC-HCC has been reported to range from 5 to 15%, and the number of NBNC-HCC patients in Japan has recently been gradually increasing (4)(5)(6)(7). It is noteworthy that the proportion of NBNC-HCC patients was ~30% in 2011, 2012 and 2013 in our hospital (1).…”
Section: Introductionmentioning
confidence: 99%
“…Curative therapies for HCC consist of liver transplantation, surgical resection (SR) and radiofrequency ablation (RFA) (1)(2)(3)(4)(5)(6)(7). The clinical outcome of HCC patients undergoing these therapies has improved substantially in recent years due to their advances.…”
Section: Introductionmentioning
confidence: 99%
“…Since the incidence of HCV-related HCC has been decreasing over the past few years due to the promotion of anti-HCV therapy [27], the observed trends might be changing due to the improved socioeconomic conditions and the development of more effective treatments for chronic liver disease, a common cause of HCC [28-30]. When assessing the usefulness of treatment for the elderly patients, life expectancy and existing comorbidities should be considered.…”
Section: Discussionmentioning
confidence: 99%